Peningkatan Pengetahuan Orang Tua Siswa, Guru dan Siswa SD Tunas Harapan Islam Medan tentang Pencegahan Pandemi Covid-19 - Nevi Yanti; Fitri Yunita Batubara; Essie Octiara; Darmayanti Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
The new corona virus epidemic (Covid-19) was declared a global pandemic on March 11, 2020 by the World Health Organization (WHO). The Covid-19 mortality rate in Indonesia of 8.9% is the highest number in Southeast Asia. Knowledge of the prevention of the Covid-19 pandemic is very important to prevent the transmission of Covid-19. The purpose of this study was to determine the level of knowledge of parents, teachers, and students of Taman Harapan Islam Medan Elementary School about the prevention of the Covid-19 pandemic. This study used a pretest questionnaire for initial data collection, then counseling was carried out on the prevention of Covid-19 and for the final data collection, a post test questionnaire was used. The results of the Mann Whitney test showed that there were differences in the level of knowledge of parents and children about Covid-19 before and after counseling (P value 0.022) and there were differences in the level of knowledge of parents and children about Covid-19 after counseling (P value 0.002). So it can be concluded that there was an influence on the level of knowledge of parents and children about the spread of Covid-19 infection. Education about preventing the spread of Covid-19 to parents of students, teachers and students of the Taman Harapan Islam Medan Elementary School can provide an understanding of the importance of preventing the spread of Covid-19 and can be passed on to their families and the surrounding environment.